Economical analysis of diagnostic study at women with inflammatory diseases of pelvis minor organs - L. Yu. Chernikova; I. D. Yevtushenko; A. V. Grishin (Бюллетень сибирской медицины, 2004)
Practice of treatment standard application experiences the certain difficulties. On the one hand, the most treatment standards lay on insufficient economical base, on the other hand, the limitation of health protection in bankroll leads to the insufficient treatment efficiency.An analysis of diagnostic study costs in Tomsk special treatment-and-prophylactic institutions has been made on the example of inflammatory pelvis minor organ diseases.The results of the investigation have shown that the character of diagnostic study of patients with inflammatory pelvis minor organ diseases differed significantly from the treatment standard. At the same time this fact defines not only the necessity of expense increase for diagnostic study but, first of all, the necessity of changes of diagnostic study structure that has been proved by modern pharmaeconomical methods.